Permanence and dropout versus self-sufficiency of university students: a challenge in quality education (2017)
Introduction. the student dropout at university level continues being a current problem that unleashes financial loss besides social and familiar ones, when academic formation goals are not achieved, which assures skillful workers for the current labor world. Objective. To analyze the permanence and dropout versus self-sufficiency of university students in the quality educative framework. Materials and methods. Population was composed by university students in the city of Barranquilla, Colombia. The registry of 2015-1 term, a sample of 322 students, from which 195 were active and 127 on dropout was taken. The work was descriptive and transactional of non-experimental design. Data collection instrument was the General Self-sufficiency scale (GSS), supported by the institutional information system of the Admissions and Registration Department. Results. It was proved that there is not a significant correlation between self-efficiency and permanence, as neither between self-sufficiency or dropout; however, a significant finding was to prove that the average of dropout's self-sufficient students resulted greater than the one of students staying in the institution. Conclusions. It was obtained that there is not a significant correlation among self-efficiency, dropout, and permanence variables.